A new species and a key to 19 species of the genus Traulia Stål, 1873 (Orthoptera: Catantopidae) from China - Cao, Cheng-Quan; Shi, Jian-Ping; Yin, Zhan (Zootaxa, 2015)
A new species of the genus Traulia Stål, 1873 namely Traulia xiai sp. nov. is described from China in this paper. The new species is similar to Traulia brachypeza Bi, 1986, but differs from the latter by the short tegmina, reaching the middle of third abdominal tergite only. The new species is also similar to Traulia ornate Shiraki, 1910, but differs from the latter by hind tibia all orange red and furculae of male absent. We think that Traulia yifengensis Wang, Xiangyu & Liu, 1997 is a valid species, not a synonym of Traulia brachypeza Bi, 1985 by Wei & Huang (2012), because the tegmina of Traulia yifengensis is very long, extending over the end of abdomen distinctly. A key to 19 species of this genus from China is also given in this paper. The type specimens are deposited in the National Museum of Natural Science, Taichung, Taiwan, China.